Evaluation of biofilms formation and corrosion of steel by microscopic techniques and electrochemical impedance spectroscopy - Viera, Marisa R. (2016)
Fil: Viera, Marisa R.. Centro de Investigación y Desarrollo en Fermentaciones Industriales. Facultad de Ciencias Exactas. Universidad Nacional de La Plata; Argentina